Charge transport in bismuth orthogermanate crystals - Bochkova, T.M.; Plyaka, S.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Current-voltage relations in bismuth orthogermanate crystals with Ag, Pt, InGa electrodes have been measured in the modes of double and unipolar injection of charge carriers. It has been shown that Bi₄Ge₃O₁₂ is relaxation type semiconductor. The appearance of the regions with negative differential resistance or sublinear rise of the current in characteristics is connected with the injection of the minority charge carriers and recombination processes in the space charge layer.